FAMILY MYCETOPHILIDAE - Oliveira, Sarah Siqueira; Amorim, Dalton De Souza (Zootaxa, 2016)
The Mycetophilidae include small fungus-gnats which life cycle is associated with fungi, especially of the larvae. The known diversity of the family in the Neotropical region is 1,145 species, but only some very few papers have been published on the Colombian species of Mycetophilidae, with records for the genera Docosia Winnertz, Paraleia Tonnoir, and Dziedzickia Johannsen. This catalogue gathers the information available on mycetophilids from Colombia, including genera and some species that for the first time are mentioned to occur in the country—as Leiella unicincta Edwards and Leiella zonalis Edwards.